Tingkat Efektivitas Lembar Kerja Peserta Didik (LKPD) Berbasis Model Pembelajaran SSCS Kelas XI SMA Negeri 1 Majene - Sudirman, Randi; Mustami, Khalifah; Rapi, Muh. (Program Pascasarjana, UIN Alauddin Makassar, 2023)
The aim of this research is to determine the level of effectiveness of Student Worksheets (LKPD) based on the Search, Solve, Create and Share (SSCS) learning model in the principles and practices of Islamic economics in class XI SMA Negeri 1 Majene. In answering this problem the author uses a type of research and development approach that adapts the 4D development model design, namely: 1) definition, 2) design, 3) development, 4) distribution, by producing a certain product. The product produced is a Search, Solve, Create and Share (SSCS) based LKPD on the principles and practices of Islamic economics. The subjects of this research were Islamic religious education teachers and class XI students at SMA Negeri 1 Majene. This research was created to find out how effective the LKPD that will be developed is. Validity data was obtained from the results of expert validators regarding the LKPD being developed, practicality data was obtained from teacher and student response questionnaires and effectiveness was obtained from learning outcome tests. The results of this research show that the validation results from expert validators of Search, Solve, Create and Share (SSCS) based LKPD teaching materials developed by researchers have met the criteria for validity, practicality and effectiveness. It is said to be effective by looking at the N-Gain test results, namely 0.71, which is in the high category. From these data it can be said that the LKPD based on Search, Solve, Create and Share (SSCS) that was developed can be said to be effectively used as teaching material in the learning process. The implication of this research is that LKPD based on Search, Solve, Create and Share (SSCS) on the principles and practices of Islamic economics is considered as one of the teaching materials that can be used in the classroom learning process. Search, Solve, Create and Share (SSCS) based LKPD on the principles and practices of Islamic economics should be tested in other schools. Abstrak Tujuan penelitian ini adalah untuk mengetahui bagaimana tingkat efektivitas Lembar Kerja Peserta Didik (LKPD) berbasis model pembelajaran Search, Solve, Create and Share (SSCS) pada materi prinsip dan praktik ekonomi Islam kelas XI SMA Negeri 1 Majene. Dalam menjawab permasalahan tersebut penulis menggunakan jenis pendekatan penelitian dan pengembangan (research and development) yang mengadaptasi desain model pengembangan 4D yaitu: 1) pendefinisian, 2) perancangan, 3) pengembangan, 4) penyebaran, dengan menghasilkan produk tertentu. Produk yang dihasilkan adalah LKPD berbasis Search, Solve, Create and Share (SSCS) pada materi prinsip dan praktik ekonomi Islam. Subjek dari penelitian ini adalah guru pendidikan agama Islam dan peserta didik kelas XI SMA Negeri 1 Majene. Penelitian ini dibuat untuk mengetahui bagaimana keefektifan LKPD yang akan dikembangkan. Data kevalidan diperoleh dari hasil validator ahli tentang LKPD yang dikembangkan, data kepraktisan diperoleh dari angket respon guru dan peserta didik dan keefektifan diperoleh dari tes hasil belajar. Hasil penelitian ini menunjukkan bahwa hasil validasi dari validator ahli bahan ajar LKPD berbasis Search, Solve, Create and Share (SSCS) yang dikembangkan peneliti telah memenuhi kriteria kevalidan, praktis, dan evektif. Dikatakan efektif dengan melihat hasil uji N-Gain yaitu sebesar 0,71 berada pada kategori tinggi. Dari data tersebut dapat dikatakan bahwa LKPD berbasis Search, Solve, Create and Share (SSCS) yang dikembangkan dapat dikatakan efektif digunakan sebagai bahan ajar dalam proses pembelajaran. Implikasi dari penelitian ini adalah LKPD berbasis Search, Solve, Create and Share (SSCS) pada materi-materi prinsip dan praktik ekonomi Islam dipertimbangkan sebagai salah satu bahan ajar yang dapat digunakan dalam proses pembelajaran di kelas. LKPD berbasis Search, Solve, Create and Share (SSCS) pada materi prinsip dan praktik ekonomi Islam sebaiknya diuji cobakan ke sekolah-sekolah lain.